Impact of COVID-19 Pandemic on Children Visiting Emergency Department for Mental Illness: A Multicenter Database Analysis from Korea - Woori Bae; Arum Choi; Seonjeong Byun; Kyunghoon Kim; Sukil Kim (MDPI AG, 2022)
We aimed to identify changes in the proportion of pediatric emergency department (PED) visits due to mental illness during the coronavirus disease 2019 (COVID-19) pandemic. This was a retrospective observational study of visits to the PED at six university hospitals from January 2017 to December 2020. We included children aged 5-17 years who were diagnosed with a mental illness. We used segmented regression analysis to identify the change in the proportion of patients with mental illness. A total of 845 patients were included in the analysis. After the first case of COVID-19 was reported in Korea, the number of PED visits significantly decreased by 560.8 patients per week (95% confidence interval (CI): −665.3 to −456.3, p < 0.001). However, the proportion of patients with mental illness increased significantly, by 0.37% per week (95% CI: 0.04% to 0.70%, p = 0.03), at this time point. Subgroup analyses revealed that emotional disorders significantly increased by 0.06% per month (95% CI: 0.02% to 0.09%, p < 0.001) during the pandemic. Our study revealed that an increased proportion of patients with mental illness visited the PED during the COVID-19 pandemic. Specifically, we identified that the proportion of emotional disorders continues to rise during this pandemic.